New Developments in T Cell Immunometabolism and Therapeutic Implications for Type 1 Diabetes - Zhang, Mengdi; Zhou, Yanyan; Xie, Zhiguo; Luo, Shuoming; Zhou, Zhiguang; Huang, Jiaqi; Zhao, Bin (Frontiers in Endocrinology, 2022)
Type 1 diabetes (T1D) is an autoimmune disease mediated by T cells and is becoming a serious public health threat. Despite the increasing incidence rate of T1D worldwide, we still lack a full understanding of why T1D develops and how T cells lost their self-tolerance in this process. Recent advances in immunometabolism have shown that cellular metabolism plays a fundamental role in shaping T cell responses. T cell activation and proliferation are supported by metabolic reprogramming to meet the increased energy and biomass demand, and deregulation in immune metabolism can lead to autoimmune disorders. Several metabolic pathways and factors have been investigated to rectify known deficiencies in several autoimmune diseases including T1D. Most of the therapeutic strategies have been concentrated on aerobic glycolysis to limit T cell responses whereas glycolysis is the main metabolic pathway for T cell activation and proliferation. The use of metabolic inhibitors, especially glycolysis inhibitors may largely leave T cell function intact but primarily target those autoreactive T cells with hyperactivated metabolism. In this review, we provide an overview of metabolic reprogramming used by T cells and summarize the recent findings of key metabolic pathways and regulators modulating T cell homeostasis, differentiation, and function in the context of T1D, and discuss the opportunities for metabolic intervention to be employed to suppress autoreactive T cells and limit the progression of β-cell destruction.